Linguistic games program to develop oral expression in early childhood education students - Cevallos Sandoval, Cintya Katerine (Universidad Ciencia y Tecnología, 2024)
This work was evaluated through an observational record that measured indicators such as Oral Expression, Clarity, Fluency, Coherence, Intonation and Vocalization, and aimed at improving communication skills in the initial stage of early childhood, crucial for human development. Using a sample of 25 children, the observations were made with an ordinal scale from 0 to 3, and the internal consistency of the items was evaluated by Cronbach’s Alpha, whose high values (0.88 to 0.97) indicate high reliability of the assessments. The results show significant variability in the individual scores, highlighting the effectiveness of child-specific pedagogical interventions. These results underscore the importance of continuous and adaptive assessment to foster optimal development of speech skills in children.